Management of Pneumomediastinum Patients in COVID-19: Rare Cases - Santosa, Andrew; Djajalaksana, Susanthy; Listyoko, Aditya; Erawati, Dini (Universitaas Brawijaya, 2024)
Background: Spontaneous pneumomediastinum in patients with confirmed cases of Covid-19 is a very rare clinical finding in the world, especially in Indonesia. This is considered an indication of concern for a more serious medical problem. Aim: This case report discusses the management of COVID-19 patients with pneumomediastinum. Case: A 30 year old man came to the hospital with the main complaint of shortness of breath and cough. The patient was diagnosed with a confirmed case of Covid-19 and received therapy using High Flow Nasal Cannula (HFNC) as a therapeutic modality. After 5 days in the hospital, the patient's shortness of breath felt increasingly severe, and he began to feel chest pain and swelling around the chest area which spread to both sides of his neck. A thorax x-ray examination showed pneumomediastinum and subcutaneous emphysema, then a chest CT scan was performed and the results showed pneumomediastinum which was thought to be caused by esophageal rupture. After we communicated with the Thoracic Surgery Department, conservative therapy was recommended. Conclusion: Covid-19 infection can cause hypoxaemic respiratory failure and acute respiratory distress syndrome, both of which can be deadly. Supplementation of high-flow nasal cannula (HFNC) oxygen therapy can be very beneficial for patients, but can cause dangerous side effects such as pneumomediastinum. Pneumomediastinum (PM) is the presence of open air in the mediastinal cavity. In this case, we suspect that the pneumomediastinum was the result of Covid-19-related alveolar damage and esophageal rupture, and not due to the use of HFNC. Pneumomediastinum complications need to be detected early, so that management can reduce associated morbidity and mortality. Keywords: Pneumomediastinum; COVID-19, HFNC